Kondisi Populasi dan Habitat monyet ekor panjang (Macaca fascicularis) - Claudya A. Dhaja; Yohanes T.R.M.R. Simarmata; Gerson Njurumana (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2019)
This study investigated the long-tailed macaque (Macaca fascicularis) population and the habitat condition currently located in the Monkey Cave Recreational Park in Tenau. The long-tailed macaques in Monkey Cave Recreational Park in Tenau were originally brought by the colonialists of the Netherlands as pets. The population was dispersed during World War II when Japanese imperialists invaded Timor island. The habitat of the macaque in Tenau has since been improved by the Tourism Office in cooperation with Kupang City’s Central agency of Forest Area Consolidation. In 1998 a land area of 0.8 ha was allocated to form a habitat for the long-tailed macaque population. Since the formation of this protected ecosystem, there has not yet been any research on the population and habitat conditions of the macaques. Data and information related to these animals can be useful to support management plans, especially for primate-based ecotourism development. This study aimed to determine the structure of these populations as well as the habitat conditions of long-tailed macaques in Monkey Cave Recreational Park in Tenau.